Impact of COVID-19 on smallholder poultry farmers in Nigeria - Bamidele, Oladeji; Amole, Tunde A. (MDPI, 2021)
In sub-Saharan Africa, most households in rural communities keep smallholder poultry, and are exposed to harsh socio-economic conditions caused by COVID-19 pandemic due to the vulnerability of their production systems to crisis. This study assessed the impact of COVID-19 on 525 smallholder poultry farmers in five states of Nigeria. The study was conducted 15 months after the onset of the pandemic in Nigeria using structured questionnaires focused on socio-demography, income, production systems, markets, and food security. Average household size increased from 6.9 before COVID-19, to 8.3 during COVID-19, representing a 20.3% increase in population growth. Over half (52.6%) of this increase was due to childbirths. Average monthly income before and during the pandemic was reduced from NGN 22,565 (USD 62.70) to NGN15,617 (USD 38.10), respectively. During the pandemic, there was a 28.4% increase in the number of farmers living below the international poverty line of USD 1.90 per day. In addition, reliance on chickens for food and income was significantly (p < 0.05) impacted by gender, location, household size, and monthly income. These results show that the COVID-19 pandemic had a significant effect on the livelihoods and food security of farmers, and the findings are essential in developing appropriate post-COVID-19 interventions for smallholder poultry production in Nigeria.